Urban design, public space and creative milieus: an international comparative approach to informal dynamics in cultural dsitricts - Costa, P. (2013)
This paper explores the relation between urban design, publicspace appropriation and the informal dynamics verified on creative milieus,from an international comparative perspective. Based on an empirical approachto urban morphology, everyday life and symbolic public space appropriation onthose areas, ten cultural quarters around the world are studied: Bairro Alto(Lisbon); La Gracia (Barcelona); Vila Madalena (São Paulo); Beyoglu (Istanbul);Marais (Paris); Oltrarno (Florence); Akihabara (Tokyo); Kreuzberg SO36 (Berlin);Capitol Hill (Seattle); and Brick Lane (London). They represent very diversesituations in terms of their historical, cultural and economic backgrounds aswell as in what concerns to the spatial conditions that support creativeclusters and the vitality and sustainability of “creative milieus”. Drawing onliterature review and on the recollection and critical interpretation of visualinformation on these areas, a comparative approach to these cases is developed,considering multiple analytical dimensions, which enable us to map andcharacterize the diversity of urban cultural districts. This may provide acontribution towards the development of a new planning agenda for dealing withurban creative dynamics and cultural quarters.